Pengaruh Ekspor Produk Halal terhadap Current Account Balance di Indonesia - Wina Annisafitri Purnama; Ilmiawan Auwalin (Universitas Airlangga, 2019)
This research aims to measuring the effects of halalproduct export on current account balance (CAB) with some of control variables such as GDP growth, national currency to US dollar exchange rate, government expenditure, real interest rate and inflation. This research is quantitative approach using ARDL model. Based on time series data in quarterly, The results of the t and F tests in this study indicate that in the long run the export of halal industrial products and government expenditures partially has a significant positive effect, inflation has a significant negative effect, while the exchange rate and GDP growth do not have a significant effect on CAB. In the short term exports of halal industrial products and government expenditure have a significant positive effect, inflation and real interest rates have a significant negative effect, while the exchange rate and GDP growth do not have a significant effect on CAB.Keywords: Halal Product Export, Current Account Balance, Halal ExportREFFERENCESAbdul-Talib dan Abd-Razak. 2013. Cultivating export market oriented behavior in halal marketing: Addressing the issues and challenges in going global. Journal of Islamic MarketingArifin dan Hadi. 2007. Membuka Cakrawala Ekonomi, Bandung: PT Setia Purna Inves.A Samuelson. Paul & William D Nordhaus 1997. Mikroekonomi. Jakarta: ErlanggaCalderon, Cesar, Alberto Chong and Norman Loayza, 2000.” Determinant of Current Account Deficit in Developing Countries,” The World Bank Policy Research Working Paper, No. 2398Fabozzi, Frank dan Franco Modigliani 1996, Capital Markets, 2nd edition, Prentice hall, New JerseyFitri, Wulansari. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Neraca Transaksi Berjalan : Studi Kasus Indonesia Tahun 1990-2011. EconomicsDevelopment Analysis JournalHandoko, Rudi (2010). Faktor-Faktor yang Mempengaruhi Kinerja Transaksi Berjalan Indonesia. Kajian Ekonomi dan Keuangan, Volume 14 No. 4 tahun 2010.Indonesia Halal Economy and Strategy Roadmap 2018/2019Karl, E Case dan Fair, C Rai. 2001. Prinsip-prinsip Ekonomi Makro. Jakarta: PrenhalindoMadura, Jeff. 2006. International Corporate Finance. Keuangan Perusahaan Internasional.Edisi 8.Buku 1. Jakarta: Salemba Empat.Saputra dan Maryatmo. 2017. Pengaruh Nilai Tukar dan Suku Bunga Acuan Terhadap Neraca Transaksi Berjalan di Indonesia Periode 2005: 1–2015: 1 (Pendekatan Error Correction Model). Diakses dari ojs.uajy.ac.id. Seran, Sirilius. 2016. Pendidikan & Pertumbuhan Ekonomi versus Kemiskinan Penduduk (Kasus Provinsi Nusa Tenggara Timur). Yogyakarta : DeepublishStudenmund. 2006. Using Econometrics: A Practical Guide. Pearson Education, Inc. Addison Wesley.Widjaja dan Ahmad Yani. (2000), Transaksi Bisnis Internasional Ekspor-Impor, Jakarta: Raja Grafindo Persada Widjajanta, Bambang., Aristanti (2007). Mengasah Kemampuan Ekonomi, Bandung : 2007.www.bi.go.id